Association between Polyunsaturated Fatty Acid Profile and Bronchial Inflammation in Bronchiolitis Obliterans - Silvija P. Jerkic; Laura Bächle; Ruth Pia Duecker; Lucia Gronau; Andreas G. Chiocchetti; Stefan Zielen; Ralf Schubert (Mediators of Inflammation)
Introduction. Bronchiolitis obliterans (BO) is a chronic lung disease, which occurs after an insult to the lower airways, in particular after airway infections or after stem cell transplantation, and which results in persistent inflammation. N–3 and n–6 polyunsaturated fatty acids (PUFA) have been shown to influence the inflammatory processes in chronic inflammatory conditions. Since BO is maintained by persistent pulmonary inflammation, a disbalanced n–6/n–3 fatty acid profile could support the inflammatory process in patients with BO and therefore, could become an approach to new therapeutic options. Methods. Twenty-five patients with BO (age: 13; 7–39) and 26 healthy controls (age: 19; 7–31) participated in the study. Lung function (forced viral capacity (FVC), forced expiratory volume 1 (FEV1), residual volume (RV)), and lung clearance index (LCI) were measured. Induced sputum was analyzed for cytology and cytokine levels (IL-1ß, IL-6, IL-8, TNF-α) using cytometric bead array (CBA). The PUFA profile was determined in the serum and induced sputum by gas chromatography. Results. Patients presented with significantly lower FVC and FEV1 as well as higher RV and LCI measurements compared to the control group. Apart from a massive airway inflammation indicated by elevated numbers of total cells and neutrophils, the CBA analysis showed significantly increased levels of IL-1β, IL-6, and IL-8. The analysis of PUFA in sputum and serum revealed a significant difference in the ratio between the n–6 PUFA arachidonic acid (AA) and the n–3 PUFA docosahexaenoic acid (DHA) (AA : DHA). Furthermore, the AA : DHA ratio significantly correlated with the inflammatory cytokines in induced sputum. Conclusion. Lung function in BO is significantly impaired and associated with uncontrolled neutrophil-dominated airway inflammation. Furthermore, the imbalance in the AA/DHA ratio in favor of n–6 PUFA demonstrates a pro-inflammatory microenvironment in the cell membrane, which correlates with the inflammatory cytokines in induced sputum and might be an option for an anti-inflammatory therapy in BO.